(untitled) (Scientific journal of the Fergana State University, 2025)
In the institute of evidence, the issue of legal consciousness encompasses ideological, psychological, and material factors from a philosophical perspective. Legal consciousness refers to the presence of legal knowledge both in a general sense and in the mind of each individual, as well as the active manifestation of this knowledge in social relations. The article also analyzes the distinctive features of the philosophical approach to the issue of legal consciousness.